Research priority setting in food and health domain: European stakeholder beliefs about legitimacy criteria and processes. (February 2019) - Timotijevic, Lada; Khan, Shumaisa S.; Raats, Monique; Braun, Susanne
Highlights: Dietary factors are important risk factors affecting population in the EU. Research and innovation (R&I) prioritisation is key to addressing these challenges. We study EU stakeholder beliefs about legitimacy of food & health R&I prioritisation. Concerns expressed about input (influence) & output (quality of decisions) legitimacy. NGOs and public sector are more concerned about input legitimacy than business sector. Abstract: Dietary factors are the most important risk factors affecting health and well-being of population in every Member State of the European Region. Finding sustainable solutions to the food and health challenges is one of the key issues that today's society urgently needs to address. Research prioritisation thus has an essential role in directing public resources to addressing these challenges. However, the processes of prioritisation among the food and health funders are rarely subject to scrutiny and the calls for democratizing science continue, as a means of enhancing both input legitimacy (with its focus on the processes of decision-making) and output legitimacy (the utility and impact of such decisions). The current study examines what conceptualisations of legitimacy (input and output) are held by the European stakeholders of the food and health research and innovation (R&I) process such as business organisations, non-governmental organisations (NGOs) and public sector organisations. We analyse stakeholder views from a series of European Awareness Scenario Workshops across nine EU countries (N = 295). The content and thematic analysis of the outputs identified six criteria determining conceptualisations of legitimacy: Influence; Representation; Procedural issues; Epistemic focus; Strategic vision; and Impact. The statistical analysis of the coded data highlighted stakeholder differences with business sector organisations being significantly less concerned about influence and representation than either NGO or public sector organisations. The results indicate that input legitimacy is of major concern to civil society and public sector actors. They reflect the wider debate about the way in which food and health R&I should be funded and policy decisions conducted, suggesting a need for better delineation of stakeholder roles and power differentials in this process. The findings are discussed with reference to the current discussions about Responsible Research and Innovation.